2016
DOI: 10.1016/j.heliyon.2016.e00186
|View full text |Cite
|
Sign up to set email alerts
|

Timing of reactive stepping among individuals with sub-acute stroke: effects of ‘single-task’ and ‘dual-task’ conditions

Abstract: Performance decrements in balance tasks are often observed when a secondary cognitive task is performed simultaneously. This study aimed to determine whether increased cognitive load resulted in altered reactive stepping in individuals with sub-acute stroke, compared to a reactive stepping trial with no secondary task. The secondary purpose was to determine whether differences existed between the first usual-response trial, subsequent usual-response trials, and the dual-task condition. Individuals with sub-acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…[24][25][26][27] Interestingly, however, when larger-magnitude perturbations are used, the resulting protective step is not consistently impacted by a secondary dual task. 12,28,29 For example, 2 studies, 12,28 showed little to no impact of a secondary task on step outcomes in stroke survivors and age-matched controls, respectively. Zettel et al 29 showed that in older adults, only mediolateral anticipatory postural responses prior to the protective step was affected by dual tasking.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Interestingly, however, when larger-magnitude perturbations are used, the resulting protective step is not consistently impacted by a secondary dual task. 12,28,29 For example, 2 studies, 12,28 showed little to no impact of a secondary task on step outcomes in stroke survivors and age-matched controls, respectively. Zettel et al 29 showed that in older adults, only mediolateral anticipatory postural responses prior to the protective step was affected by dual tasking.…”
Section: Discussionmentioning
confidence: 99%
“…The stroke patients with FOF avoid different activities which may lead to restricted mobility, reduced functional capabilities, and loss of functional independence. It is noteworthy that this avoidance leads to the muscle atrophy and weakens the balance performance which finally increases the risk of falling and FOF (Schinkel-Ivy, Inness, & Mansfield, 2016). Various studies among stroke population have shown that the severity of disease, the balance impairment, and the FOF may be related to the lower physical activity levels (Goh, Nadarajah, Hamzah, Varadan, & Tan, 2016;Rosén, Sunnerhagen, & Kreuter, 2005;Shaikh & asghar Hosseini, 2016).…”
Section: Introductionmentioning
confidence: 99%